Herpes simplex encephalitis: A new type of "ICU-acquired infection"?. Issue 3 (March 2020) - Hauw, Fabien; Dinkelacker, Vera; Jaquet, Pierre; Vespignani, Hervé; Grégoire, Charles; Perrin, Mathilde; Engrand, Nicolas
Abstract: Purpose: Although it is a well-known disease, the occurrence of Herpes simplex encephalitis (HSE) during a hospital stay may render the diagnosis particularly challenging. The objective of this report is to alert clinicians about the diagnostic pitfalls arising from hospital-developed HSE. Materials and methods: Clinical observation of one patient. Case report: An 87-year-old male was admitted to the Intensive Care Unit (ICU) because of respiratory failure due to an exacerbation of myasthenia gravis. After corticoids and azathioprine treatment, his clinical condition improved, allowing weaning from mechanical ventilation. One month after admission, while still hospitalized in the ICU, the patient developed fever and confusion. In the context of confounding factors, HSE was not suspected before a convulsive status epilepticus occurred, resulting in a significant delay in treatment. Diagnosis was confirmed by PCR-analysis in the cerebrospinal fluid. Serological status confirmed reactivation of prior herpes simplex infection. The patient died one week after the onset of confusion. Conclusions: Hospital-"acquired" HSE must be suspected in case of new neurologic symptoms associated with fever, even in ICU-hospitalized patients. The diagnosis is made even more difficult by nonspecific symptoms due to previous diseases, leading to an even more severe prognosis in those vulnerable patients. Abstract : Electrophysiology; Infectious disease; Neurology; Neurosurgery; Intensive care medicine; Herpes simplex Encephalitis; Intensive care; Immunosuppression; ICU acquired Infection; Herpes simplex reactivation